2001
DOI: 10.1093/carcin/22.10.1607
|View full text |Cite
|
Sign up to set email alerts
|

p53-independent apoptosis mediated by tachpyridine, an anti-cancer iron chelator

Abstract: Iron is involved in essential biochemical reactions ranging from respiration to DNA synthesis. Consequently, iron deprivation has been proposed as a strategy for inhibition of tumor cell growth. We recently described a novel iron chelator, tachypyridine [N,N',N"-tris(2-pyridylmethyl)-cis,cis-1,3,5-triaminocyclohexane], and demonstrated that it not only inhibited growth of cultured tumor cells, but was actively cytotoxic. Here we explore the mechanisms underlying tachpyridine cytotoxicity. Using several criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 43 publications
1
64
1
Order By: Relevance
“…As shown in Figure 8a, the level of ferritin was found to be decreased by MCGA3 treatment, which is evident at 8 h after treatment, whereas TfR1 protein level was more rapidly elevated by MCGA3 treatment, which is evident at 2 h and gradually increased in a timedependent manner. Studies have shown cross-link between intracellular iron deprivation-induced hypoxia and p53-independent p21 upregulation (Abeysinghe et al, 2001;Baby et al, 2003). Similarly, our results also shows, MCGA3 treatment induces p21 and TfR1 protein levels in timedepended manner (Figures 4a and 8a).…”
Section: Mcga3 Inhibits Uva-initiated Survival Signalssupporting
confidence: 88%
See 1 more Smart Citation
“…As shown in Figure 8a, the level of ferritin was found to be decreased by MCGA3 treatment, which is evident at 8 h after treatment, whereas TfR1 protein level was more rapidly elevated by MCGA3 treatment, which is evident at 2 h and gradually increased in a timedependent manner. Studies have shown cross-link between intracellular iron deprivation-induced hypoxia and p53-independent p21 upregulation (Abeysinghe et al, 2001;Baby et al, 2003). Similarly, our results also shows, MCGA3 treatment induces p21 and TfR1 protein levels in timedepended manner (Figures 4a and 8a).…”
Section: Mcga3 Inhibits Uva-initiated Survival Signalssupporting
confidence: 88%
“…Therefore, we initially hypothesized that the ROSscavenging and iron-chelating potential of MCGA3 may play a role in the p21 induction by providing a hypoxic condition. Recent studies (Carmeliet et al, 1998;Abeysinghe et al, 2001;Goda et al, 2003) have shown that HIF-1a-involved p21 transcriptional activation without p53 transcriptional function. Our p21-promoter assays clearly reflect the p53-independent, Sp1-dependent transcriptional activation of p21 by MCGA3.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of chelators at inhibiting tumor growth are probably mediated through their action on many unique targets (e.g., Nip1, etc.) (19,37,38) and cannot be explained only by increased Ndrg1.…”
Section: Discussionmentioning
confidence: 95%
“…Because numerous tumors contain functionally defective p53, anticancer agents that induce apoptosis in a p53-independent manner must be developed (19)(20)(21)(22). Hence, we examined whether the DpT chelators can act independent of p53 apoptotic pathways.…”
Section: Sensitivity Of Tumor Cells To Dpt Chelators Is Independent Omentioning
confidence: 99%
“…[48] Tumor cells, as compared with their normal counterparts, frequently exhibit increased uptake and utilization of iron, as evidenced by an increase in transferrin receptors at the cell surface. [49][50][51] Additionally, cancer cells are sensitive to the effects of iron chelators because of the critical requirement for iron in proteins that play essential roles in DNA synthesis and energy production. [52,53] Such studies have led to iron chelation therapy to clinically treat some tumors.…”
Section: Introductionmentioning
confidence: 99%